Letter - Joint Strike Committee, Grantham, 7 May 1926 (page 1) (Grantham)
1926-05-07 "Letter - Joint Strike Committee, Grantham, 7 May 1926 (page 1)" [g0360001.jpg], 7 May 1926, Joint Strike Committee, Grantham Local Organisation